CONCOMITANT CARDIOVASCULAR DISEASES AND ANTIHYPERTENSIVE TREATMENT IN OUTPATIENT PRACTICE (BY THE RECVASA REGISTRY DATA) - M. Loukianov (Столичная издательская компания, 2017)
Aim. To study a pattern of concomitant cardiovascular diseases (CVDs) and to estimate particularities and quality of medical antihypertensive therapy in hypertensive patients in real outpatient practicewith a help of the Registry in Ryazan region.Material and methods. A total of 3690 patients with hypertension, ischemic heart disease, chronic heart failure and atrial fibrillation, who had attended general practitioners and cardiologists of3 outpatient clinics in Ryazan city, were enrolled in the outpatient Registry of cardiovascular diseases (RECVASA). The diagnosis of hypertension was recorded in 3648 of 3690 (98.9%) outpatientcharts, 28.1% of the subjects were men and 71.9% - women.Results. A total of 2907 (79.7%) of 3648 patients had combination of hypertension with other CVDs. Combination of 3-4 cardiovascular diagnoses was registered in 63.8% of the cases. 11.5%and 9.5% of the patients had a history of myocardial infarction and cerebral stroke, respectively. Diagnosis of hypertension was verified in 448 of 450 randomized hypertensive patients (99.6%).The incidence of prescription of one and two antihypertensive drugs (AHDs) was 25% and 39%, respectively, of 3 AHDs - 21%, 4 and more - 2%. AHDs were not prescribed in 13% of hypertensivepatients.The mean number of prescribed AHDs was 1.73. The mean incidence rate of target blood pressure achievement was 26.1%.We have noted insufficient ACE inhibitors/angiotensin receptor blockers (ARB) and beta-blockers prescription in different concomitant CVDs. Patients with 3-4 cardiovascular diagnoses were moreoften prescribed combined antihypertensive treatment.Prescription of ACE inhibitors/ARB, beta-blockers and thiazide diuretics combination was preferable in 74.1% of the cases, when taking into account absolute and relative contraindications for betablockersuse - in 64.0%. 15.2% of the hypertensive patients used reimbursed drugs for CVDs at the moment of the Registry enrollment as compared with 39.2% in previous years (p<0.05).Conclusion. The RECVASA study data allowed revealing high incidence of concomitant CVDs in hypertensive patients, insufficient use of combined antihypertensive treatment, including AHDs withproved favorable influence on prognosis. Achievement of concordance of medical treatment to national and international guidelines, taking into account concomitant CVDs, and optimization ofpatients' coverage with reimbursed drugs are the main reserves for antihypertensive treatment quality improvement.